Peningkatan Literasi Tentang Bahaya Seks Bebas Terhadap Kesehatan Reproduksi Pada Mahasiswa Keperawatan Universitas Mulawarman - Rita Puspasari; Sholichin; Ruminem; Mayusef Sukmana; Dwi Nopriyanto (Fakultas Kedokteran, Universitas Mulawarman, 2023)
Abstract The phenomenon of sexuality and adolescent reproductive health is very important to understand, but there is still a lack of information about these reproductive health issues because discussing them with adolescents is still considered taboo. The problem of promiscuous sexual behaviour in adolescents must be addressed by providing health education and education, as well as the effects of diseases that can be caused. In addition, efforts are needed to control premarital sexual habits. The problem of free sex is a major concern that we must prevent in the adolescent environment, because the impact will interfere during the life cycle of the teenager until he/she becomes an adult. the purpose of this community service activity is to increase Knowledge about Free Sex Prevention and have a positive attitude towards sex and activities that can divert attention from sexual needs in adolescents. Literacy improvement is carried out in the form of delivering material about the dangers of free sex on adolescent reproductive health. The implementation is in the form of providing material as a form of soft skills so that sexual behaviour that occurs among students can be controlled and does not have bad consequences for students. . Keywords: Improvement, Literacy, Free Sex, Student